Evaluating the Effectiveness of a General English (GE) Program with Peer Tutoring in Enhancing Freshmen's Speaking Skills and Communication Confidence - Dwimaulani, Astrid; Ali, Muhammad Usman; Saputra, Ahmad Yudi (Jurnal Ragam Pengabdian, 2026)
This research sought to assess the effectiveness of the General English (GE) Program in enhancing the English-speaking skills and communication confidence of freshmen at Hamzanwadi University. A convergent design utilising a mixed-methods approach was implemented, engaging 40 first-year students participating in the 2025/2026 General English Program. Quantitative data were gathered using a one-group pretest-posttest methodology, and qualitative data were acquired using semi-structured interviews. The results indicated that the average speaking score rose from 64.00 in the pretest to 74.12 in the posttest, signifying a 15.81% enhancement. Interview findings indicated that students exhibited increased confidence in their English communication skills and regarded Communicative Language Teaching (CLT) and peer tutoring as efficacious methods for fostering an engaged and supportive educational atmosphere. Despite the persistence of many hurdles, the results suggest that the General English Program significantly improved students' speaking skills and communication confidence. The research indicates that combining Communicative Language Teaching with peer tutoring may serve as an effective teaching framework for English preparation courses in higher education.